2019
DOI: 10.4196/kjpp.2019.23.5.381
|View full text |Cite
|
Sign up to set email alerts
|

Onion peel extract and its constituent, quercetin inhibits human Slo3 in a pH and calcium dependent manner

Abstract: Sperm function and male fertility are closely related to pH dependent K + current (KSper) in human sperm, which is most likely composed of Slo3 and its auxiliary subunit leucine-rich repeat-containing protein 52 (LRRC52). Onion peel extract (OPE) and its major active ingredient quercetin are widely used as fertility enhancers; however, the effect of OPE and quercetin on Slo3 has not been elucidated. The purpose of this study is to investigate the effect of quercetin on human Slo3 channels. Human Slo3 and LRRC5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…One opinion considers that SLO3 is the main potassium channel in human sperm. (Wijerathne et al, 2017(Wijerathne et al, , 2019. Therefore, we think that IbTX acts on the SLO1 potassium channel when human sperm are treated with this inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One opinion considers that SLO3 is the main potassium channel in human sperm. (Wijerathne et al, 2017(Wijerathne et al, , 2019. Therefore, we think that IbTX acts on the SLO1 potassium channel when human sperm are treated with this inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…IbTX is considered a SLO1 specific inhibitor with the IC50 at about 2–10 nM (Yu et al, 2016). Wijerathne et al heterologously expressed hSlo3 and hLRRC52 in HEK293 cells and found that 100 nM IbTX does not affect the I hSLO3 (Wijerathne et al, 2017, 2019). Therefore, we think that IbTX acts on the SLO1 potassium channel when human sperm are treated with this inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional medicine has been extensively used to ameliorate men's health problems in Korea (Jiang et al, 2017). In particular, ion channel‐targeted herbal medicines and their mechanisms of action in sperm for treating male infertility are being researched (Chae et al, 2017; Wijerathne et al, 2019). Our study demonstrated the positive action of PJE on sperm motility via the sperm hHv1 proton channel.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, KSper plays a principal role in mouse sperm but is not clear in human sperm 37,92 . It can hyperpolarize the membrane potential from about −40 mV in the resting state to about −60 mV after being activated under alkaline conditions, 37,94,95 which decreases the electrochemical driving force of Ca 2+ to influx through CatSper channels 40,96 . If KSper is antagonized by inhibitors, the sperm will not show capacitation‐dependent hyperpolarization of the cell membrane 97 .…”
Section: Mutual Regulation Mechanism Of Ion Channelsmentioning
confidence: 99%